EDUCATIONAL INTERVENTIONS FOR CAREGIVERS OF PEOPLE WITH HEART FAILURE: A SCOPING REVIEW. - Feitosa, Rayana Pereira; Nepomuceno, Adriana Meira Tiburtino; Pereira, Francilene Jane Rodrigues; Martins Wilson, Ana Maria Miranda; Neto, Omar Pereira de Almeida; de Sousa, Mailson Marques; Pontes, Maria de Lourdes de Farias (Texto & Contexto Enfermagem, 2025)
Objective: to map the evidence on educational interventions aimed at caregivers of people with heart failure. Method: scoping review conducted in accordance with the Joanna Briggs Institute guidelines, between April and July 2024, with the research question: "What evidence is available on educational interventions for caregivers of people with heart failure?" Publications were collected from reference databases and gray literature by two independent reviewers, applying inclusion and exclusion criteria. A form drawn up by the authors was used for methodological extraction and analysis, and the results were described according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Results: a total of 19 studies were included, most of them from the United States and carried out in the last Ave years by nurses. The main interventions identified include: verbal guidance sessions, written materials, multimedia resources, mobile application tools, sending emails and reports to caregivers and health professionals, as well as telephone contact, the latter being widely used. The results ranged from increased knowledge about the syndrome and confidence in care to improvements in the dimensions of self-care, quality of life, family functioning, interpersonal relationships, behavioral changes, a reduction in adverse events and changes in sleep patterns. Conclusion: the review demonstrates the importance of educational interventions centered on the patient/ caregiver dyad. It emphasizes the role of nurses in implementing strategies aimed at promoting caregiver knowledge in order to optimize health outcomes in the dyad and reduce hospital readmissions due to decompensation of heart failure.